(untitled) (Ustozlar uchun, 2026)
This article deals with “Leksikologiya” the Uzbek folklore in teaching young learnersand using interactive ways of conducting sessions. Key words: functional literacy, reading literacy, pedagogical technologies, texttechnology, methodical.